The role of university environment in promoting entrepreneurial behavior: evidence from heterogeneous regions in Brazil - Anne Kathleen Lopes da Rocha; Gustavo Hermínio Salati Marcondes de Moraes; Bruno Brand\~ao Fischer (Innovation & Management Review, 2022)
Purpose - The purpose of this study is to evaluate the microfoundations of student entrepreneurship, a cornerstone of innovation ecosystems. To this end, this paper assesses how perceived university support for entrepreneurship influences entrepreneurial characteristics and intentions in students enrolled at Amazonas and S\~ao Paulo State Universities. Design/methodology/approach - A quantitative approach based on multivariate data analysis using confirmatory factor analysis and structural equation modeling was applied to a sample of 420 respondents. Findings - Results indicate that the university environment positively influences entrepreneurial behavior and intention in students. Nonetheless, further integration between academia and external dimensions of the ecosystems is necessary to drive more intense entrepreneurial activity in students. The educational contexts of Amazonas and S\~ao Paulo present significant differences in the relationship between entrepreneurial characteristics and entrepreneurial intention with a stronger influence found for Amazonas. This finding suggests a relative lack of propensity of students from S\~ao Paulo to engage in entrepreneurial venturing. Research limitations/implications - The main limitations involve the use of non-probabilistic sampling procedures and students' heterogeneity in terms of academic seniority. Practical implications - This research offers guidance for policies targeting the generation of entrepreneurial activity in universities embedded in developing countries' innovation ecosystems and facing distinct levels of socioeconomic development. Originality/value - This research presents a novel analysis of the microfoundations driving student entrepreneurship within different educational contexts in a developing country. Results highlight the necessary conditions for universities to foster entrepreneurial activity and, incidentally, feed innovation ecosystems with entrepreneurial talent.
Keywords: 650; Brazil; Entrepreneurial characteristics; Entrepreneurial intention; Innovation ecosystems; Structural equation modeling; Student entrepreneurship; University